How cybercrime sentiment shapes mobile banking adoption in Islamic banking - Kornitasari, Yenny; Sura, Langlang Jati; Dewi, Dita Nurul Aini Mustika (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study aims to identify the factors influencing the adoption of mobile banking in the context of cybercrime issues in digital banking services by focusing on a case study of Bank Syariah Indonesia (BSI) customers.Methodology – This study examined five independent variables as mediators: cybercrime issue sentiment, security perceptions, convenience, digital literacy, cybersecurity awareness, and trust. It involves 100 BSI customer respondents and is analyzed using the SEM-PLS method.Findings – The findings indicate that Cybercrime issue sentiment and perceived security positively impact trust. However, this trust does not influence mobile banking adoption, suggesting that other factors may dominate adoption decision-making. Convenience and cybersecurity awareness affect mobile banking adoption, whereas digital literacy does not.Implications – Cybercrime is a crucial aspect of mobile banking usage, making customer awareness essential. To increase customer trust, BSI needs to strengthen and enhance digital security and educate customers about cybersecurity risks. Improving the convenience of mobile banking services is crucial to attracting more users. Cybersecurity awareness is also essential; therefore, BSI needs to conduct educational programs and campaigns to improve digital literacy and reduce the negative impact of cybercrime.Originality – The implications provide insights for banks, especially BSI, in maintaining customer trust and increasing mobile banking adoption. The results are expected to assist customers and BSI in focusing on cybersecurity, protecting personal data, and enhancing user convenience. Understanding the factors influencing mobile banking adoption in the continually evolving digital banking environment can help banks take relevant action and focus on customer needs.